Agricultural extension services for agriculture risk management through ICTs in Malaysia - Ali, Muhammad; Man, Norsida (University Community Transformation Centre, Universiti Putra Malaysia, 2017)
Agriculture Extension is considered as a major development partner in the agriculture development process. Extension services are rendered to help the farmers in different dimensions for the smooth flow of agricultural activities. As the current scenario has breeds many problems in the agriculture management process, so potential of ICTs have been attracted into this sensitive discipline. In this regard, an empirical study was conducted in four nature sensitive areas of Malaysia to assess the extension services dispensed for agriculture risk management keeping in view the digital technologies by the field staff. There were 360 farmers selected through stratified random sampling technique. The results reveal that visits paid by extension staff were mostly on annual or bi annual basis as reported by most of the farmers. Farmers reported that they got information from extension staff about use of ICTs for disaster information which is still less than required. Still most of the farmers felt that they were failed to get support from extension field staff to integrate ICTs for proper management of agriculture risks. Farmers also highlighted that extension staff knowledge is not at par so they need improvement. Thus, it can be inferred that public and private sector should initiate various training programmes firstly for the staff and then diffuse various management skills and techniques into farmer fields for better agriculture risk management and also incorporate the digital essence through ICTs. Frequency of visits may also require to be improved for effective technology transfer. As a result, not only socio-economic condition of farmers would be improved but also challenges like climate change can be handled.